Global development finance country tables - World Bank (Washington) (Washington World Bank, 2000)
Global development finance 2000 provides a comprehensive look at external debt and financial flows to developing countries.It consists of two volumes:Analysis and summary tables and country tables.Global development finance 2000 is an invaluable resource
Keywords: Finance; Finance-Statistics